The Quality of Pain Treatment in Community-Dwelling Persons with Dementia - Jiwen Li (Dementia and Geriatric Cognitive Disorders Extra, 2015)
Background/Aims: Despite pervasive and debilitating pain among elders, it is underassessed and undertreated; and cognitive impairment can add challenges. We assessed the quality of pain care for community-dwelling elderly patients with dementia. Methods: We phone interviewed 203 Veterans Affairs primary care outpatients with dementia and pain and reviewed medical records to score 15 quality indicators of pain assessment and management. Results: Pain assessment was documented for 98%, and a standard pain scale was used for 94%. Modified pain scales were rarely used. Though 70% self-reported pain of ‘quite bad' or worse, charts documented no pain in 64%. When pain was identified, treatment was offered to 80%; but only 59% had a follow-up assessment within 6 months. Nonpharmacological interventions were underused. Conclusion: Community-dwelling elders with dementia are underdiagnosed and undertreated for pain.